TRABAJADORES SANOS EN ORGANIZACIONES SANAS: ANÁLISIS SOBRE LAS PRÁCTICAS ORGANIZACIONALES SALUDABLES EN UN GRUPO EMPRESARIAL DEL SECTOR FARMACÉUTICO DE LA CIUDAD DE GUAYAQUIL. - Villavicencio Yulán, Mónica Anabell (2017)
The main purpose of this research is to determine if there is a relationship between the healthy organization practices proposed in the Hero Model (Healthy and Resilient Organizations) with the psychosocial health of the employees and the economic benefits achieved by a pharmaceutical business group in the city of Guayaquil. The sample consisted on the employees of these organizations. (N=155). Based on Pearson's correlation coefficients between the variables of the HERO Model's Resources and Practices component and the Psychosocial Health Increase, as well as the increase in the economic benefits obtained by the organization, you can conclude that there is a direct and moderate relationship between the independent variables analyzed. It is important to mention that the level of significance for all independent variables is less than 0.05 which indicates that there is no significant evidence to say that there is no relationship between the variables detailed above.